Experimental and Theoretical Study of 4-Methylaminoantipyrine with Divalent Metal Ions - Ibrahim, Farah M (Al-Nahrain Journal of Science, 2018)
Co2+, Ni2+, Cu2+ complexes with 4-methylaminoantipyrine (MAP) were synthesis and characterized by IR, UV-Vis., thermal analysis, CHNO-S analysis, magnetic susceptibility, conductivity measurements and this work includes a theoretical study of MAP complexes where it was done by the program of hyperchem8.0.7 using semi-empirical calculations. The PM3 method at 298 K used to calculate geometric properties, binding energy (ΔEb), heat of formation (ΔH○f), total energy (ΔEtot.), ultraviolet and vibrational data of the MAP complexes. The comparing of experimental data with theoretical data gave good results, so the square planar geometry suggested for complexes.